Sex-related short-term blood pressure variability differences in kidney transplant recipients. Issue 6 (27th October 2022) - Korogiannou, Maria; Alexandrou, Maria-Eleni; Sarafidis, Pantelis; Pella, Eva; Theodorakopoulou, Marieta P.; Xagas, Efstathios; Argyris, Antonis; Protogerou, Athanase; Boletis, Ioannis N.; Marinaki, Smaragdi
Abstract : Objective: Kidney transplant recipients (KTRs) display higher cardiovascular morbidity and mortality than the general population. Increased short-term blood pressure variability (BPV) is associated with a higher risk of adverse cardiovascular outcomes in chronic kidney disease (CKD). The aim of this study is to investigate sex differences in short-term BPV in KTRs. Methods: In total, 136 male and 69 female KTRs with valid 24 h ambulatory blood pressure monitoring were included in this analysis. Systolic and diastolic BPV indices [SD, weighted SD (wSD), coefficient of variation (CV), average real variability (ARV) and variability independent of the mean (VIM)] were calculated with validated formulas for the 24 h, daytime and nighttime periods. Results: Age, time from transplantation surgery and history of major comorbidities did not differ between men and women. During the 24-h period, systolic BPV indices did not differ between men and women (SBP-ARV: 9.4 ± 2.2 vs. 9.9 ± 2.5; P  = 0.212). During the daytime period, SBP-CV and SBP-VIM were significantly higher in females compared with male participants (SBP-CV: 9.9 ± 2.4 vs. 11 ± 3.1%; P  = 0.022 and SBP-VIM: 12.6 ± 3.0 vs 14.2 ± 3.9; P  = 0.008); daytime SBP-SD and SBP-ARV, and all studied indexes during nighttime did not differ between groups. No significant between-group differences in 24 h and daytime diastolic BPV indices were detected. Nighttime DBP-CV was marginally higher in men (12.0 ± 3.6 vs. 11.4 ± 4.0; P  = 0.053); the rest nighttime diastolic BPV indices measured were also nonsignificantly higher in men. Conclusion: In conclusion, 24-h systolic and diastolic BPV parameters did not differ between male and female KTRs, but short-term BPV over the respective day- and nighttime periods showed different trends in men and women. Further studies are needed to examine possible differences in long-term BPV in KTRs.